The effects of global populism: assessing the populist impact on international affairs - Daniel F. Wajner; Sandra Destradi; Michael Zürn (International Affairs, 2024)
With the global rise to power of populist leaders over the past decade, research on populism, including its international implications, has flourished. However, we still lack a nuanced understanding of the international effects of this new populist wave. The special section that this article introduces seeks to bridge this gap by systematically examining three types of international effects of populism. One group of contributions addresses the impact of populism on the processes of foreign policy-making in countries governed by populists (politics). Another group focuses on effects in terms of foreign policy agenda and its substantive outcomes (policies). A third group of contributions studies the impact of populism on states' stances towards international institutions (international polity). This introduction proposes a theoretical framework that takes into account the existent diversity among populist governments, specifically addressing how the more or less authoritarian character of populism explains variations in international outcomes across politics, policies and polities. A better understanding of these varied characters and effects can contribute new insights to lively debates about the potential challenges posed by populism and populists in the contemporary international order, and the prospects for mitigation.
Keywords: 320